Treatment of Hyperuricemia with Thlaspi Bursa Pastoris 6CH: A Randomized, Open-Label, Equivalence Trial - Koushik Bhar (Journal of Applied Sciences and Clinical Practice, 2024)
Background: Hyperuricemia (HU) remains a priority research area in every medical science, including complementary and alternative medicine interventions and homeopathy; however, the research evidence is limited. In homeopathy, Thlaspi bursa pastoris (TBP) is considered to be a potential treatment option in HU.